PERAN UMAT ISLAM DAN HINDU DALAM KONSERVASI LINGKUNGAN BERBASIS KITAB SUCI (AL-QUR’AN DAN WEDA) DI KLUNGKUNG, BALI - Qardlawi, Muhammad Yusuf (FIKRUNA: Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2025)
This study examines the role of Muslims and Hindus in environmental conservation in Klungkung, Bali, emphasizing the values of sacred scriptures as a theological foundation. The study employs a qualitative method using interviews, observations, and document analysis. The findings indicate that the concept of khalifah in Islam and Tri Hita Karana in Hinduism play a crucial role in shaping ecological awareness. Collaboration between Muslim and Hindu communities in Klungkung in environmental conservation practices has been proven to strengthen social harmony and environmental sustainability. This research provides insights into the importance of religious values in supporting sustainable environmental policies.